Agricultura familiar e sucessão hereditária: estudo de caso no município de Morro Redondo, RS - Costa, Maria Regina Caetano (2006)
Familiar agriculture joins different situations and for its reproduction must get adequate strategies according to the environment where it is inserted. About succession process, this situation is not different. Nowadays the less quantity of children and rural exodus reach the youngest population stratus. Because of that the population grows older, added to a crescent process of masculine predominance because of feminine predominance in migratory flows. But the present scenery reserves other changes and difficulties about hereditary succession in familiar agriculture. This happens because certain properties suffer obstacles to find successors before the less quantity of children or the disinterest of young people to assume their farmer condition. It is not rare the appearance of conflictive situations, although this is a crucial moment of several rural families trajectory. In this way the reality nowadays shows new scenery where the reference that guided farmer’s choices changes totally. Agrarian activities suffered very important changes like: country urbanization, low agrarian returns and other factors that together contribute for the crisis of expectations that several rural families have. This work examines these questions considering a recent inter-institutional investigation done by UFPel's Agrarian Social Sciences Department and the UFRGS´ Postgraduate Program that involved the application of 62 questionnaires and did 33 semi-structured interviews. Base on analysis information and specific theory was possible to observe an expectation crisis in familiar agriculture at Morro Redondo County. About hereditary succession, is possible to reveal that beyond women, the man are leaving the farmers too, searching for better way of life. The education continues to serve as a passport for those who want to leave the familiar property. Because of absence of professional opportunities for young people, becomes more and more difficult to find a successor for familiar unities.